PERAN TENAGA KESEJAHTERAAN SOSIAL KECAMATAN (TKSK) TERHADAP PENANGANAN LANSIA DI KECAMATAN KEPULAUAN SANGKARRANG KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The purpose of this study is to: (1) describe the role of Subdistrict Social Welfare Workers (TKSK) in The Handling of the Elderly in The Sangkarrang Islands District and (2) describe the supporting and inhibiting factors for the implementation of the role of District Social Welfare Workers (TKSK) towards the Handling of the Elderly in the Sangkarrang Islands District. This research is qualitative research. The results of the research obtained include: (1) The role of TKSK in the Sangkarrang Islands District, Makassar City in handling the Elderly is quite good, namely the role of TKSK as a coordinator, namely coordinating local governments such as Lurah and community leaders in providing social assistance to the elderly. The role of TKSK in motivating is to always provide assistance to people with social welfare problems such as the elderly when given assistance by the Makassar City Social Service office and the province of South Sulawesi, where TKSK always accompanies the elderly both when coaching and after coaching, The role of TKSK as an administrator is to verify first. convey to the beneficiaries to divide the social assistance according to the data obtained by the Social Service. (2) Supporting factors for the role of TKSK in the Sangkarrang Islands District, Makassar City, namely that there are institutions that play a role in supporting the role of Subdistrict Social Welfare Workers (TKSK) in the Sangkarrang Islands District, Makassar City such as Corporate Social Responsibility (CSR), Karang Taruna and the Village Community Resilience Institute (LKMD). Meanwhile, the inhibiting factor is that the number of officers is still very minimal so many work or work programs from TKSK are not carried out optimally.